PENGARUH INFUSA DAUN KELOR (Moringa oleifera Lamk) TERHADAP PERTUMBUHAN MIKROBIOLOGI DAN ORGANOLEPTIK DAGING BABI GILING SEGAR - Ka'auni, Maria Taroci; Kallau, Novalino H. G.; Wuri, Diana Agustiani (JURNAL KAJIAN VETERINER, 2020)
Moringa oleifera Lamk is a shrub with a height of 7-11 m and thrives from the lowlands to an altitude of 700 m above sea level. Moringa can grow in tropical and subtropical areas on all types of soil and is resistant to dry spells for 6 months. Its high nutritional value, properties and benefits have earned Moringa the nickname Mother's Best friend and the Miracle Tree. In addition, moringa plants also have benefits as antioxidants and antimicrobials so that they can be used as preservatives. This study aims to determine the benefits of adding Moringa oleifera Lamk leaf infusion to the quality of pork minced meat.This research is an experimental laboratory research. The samples used in this study were 48 samples of ground thigh pork (biceps femoris), and this study used a fully randomized design factor pattern.The quality parameters of the meat samples examined are color, the smell, texture, pH, Postma test and Total Plate Count (TPC). The results showed that the addition of moring leaf infusion changed color, aroma an d eczema. The Postma test shows that the K3 group can last up to 6 hours. The TPC value in the K3 group is below the SNI contamination limit for 6 hours.